“Viver outramente”: moradia, condições de vida e a produção da alteridade dos bolivianos em São Paulo - Pucci, Fabio Martinez Serrano (2016)
The major motivation behind this project is the concern for the living conditions of Bolivians in the Municipality of São Paulo. The main aim is to identify, analyze and establish relations among the formation of Bolivian territories in the city, the different, yet precarious housing solutions, and the levels of access to social policies and public services these immigrants have. The main hypothesis is that the lack of documentation, the length of stay in the country, the informal working agreements in the clothing industry and the different habits and culture of these immigrants lead to the precarious housing conditions, the exclusion from the formal housing market and social policies and the production of the otherness. The following theoretical references were used: Norbert Elias, Sayad, Truzzi, Castells, Sennet, Muniz, Patarra and Véras. Both quantitative and qualitative methods were combined for this research. Statistics were relevant for the empirical data collected, which served as the basis for mapping the city according to the specific objectives of the research, resulting in the identification of important Bolivian territories. Consequently, with a view to conducting the interviews, the addresses where the Bolivians and the different groups of people they live with were selected – which is the case of their Brazilian neighbors and the community health workers in the surveyed districts (Brás and Grajaú). The choice of the selected districts was made taking into account the distinct concentrations of Bolivians they comprise, both in terms of strategies for the access to housing – in Brás, they generally rent tenements, while in Grajaú they are more likely to buy their own homes, as well as their strategies of dissociation from stigmas related to the Bolivian culture – in Brás they are more stigmatized. Nonetheless, the dissociation from these stigmas results in individual strategies of integration, which prevents them from altering the ethnic structures and power relations among the groups. Lastly, the service of the community health workers is better adapted to the immigrants in Brás, despite the fact that their neighbors do not welcome their presence in the local health centers. Thus, a full integration of these immigrants requires the adoption of policies to combat discrimination